Common Causes of Congenital Deafness Diagnosed on Computed Tomography and Magnetic Resonance Imaging in a Tertiary Care Diagnostic Center in Southern Punjab - Aziz, Mubashrah; Latif, Atif; Sadiq, Nousheen; Aziz, Musfirah; Hakim, Abdul; Khan, Nadia (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the causes of congenital deafness in children presenting to a tertiary care diagnostic center in Southern Punjab. Study Design: Analytical cross-sectional study. Place and Duration of Study: Department of Radiology, Combined Military Hospital, Multan, Pakistan, from Aug 2021 to Jul 2023. Methodology: A total of 56 children, <12 years of age, belonging to either gender, who presented with the complaints of congenital deafness were included in the study. Demographic data of all patients and further necessary audiological tests were noted; they were referred for high-resolution computed tomography (HRCT) and magnetic resonance imaging (MRI) of temporal bone and findings were interpreted by consultant radiologist. Results: Out of 56 patients, 30(53.6%) patients were males and 26(46.4%) were females. Mean age was 2.80±0.83 years with consanguinity noted in 43(76.8%) cases. The prevalence of inner ear malformations was found to be present in 7(12.5%) cases. Most common anomaly noted was Cystic Hypoplastic Cochlea (CH)-III in 4 out of 56 cases (7.1%), followed by CH-II (n=2, 3.6%) while enlarged vestibular aqueduct was found only in 1 case. Furthermore, out of 7 patients, 14.3% anomalies were detected in right ear, 28.6% in left ear and 57.1% in both ears. Conclusion: These findings underscore the value of high-resolution temporal bone HRCT and MRI in the etiological workup of pediatric congenital deafness and highlight the need for early imaging-based evaluation to guide appropriate counselling, rehabilitation planning, and future preventive strategies in populations with a high rate of consanguinity.